Methodology for fast development of digital solutions in integrated continuous downstream processing - Andersson, Niklas; Fons, Joaquín Gomis; Isaksson, Madelène; Tallvod, Simon; Espinoza, Daniel; Sjökvist, Linnea; Andersson, Gusten Zandler; Nilsson, Bernt (Biotechnology and bioengineering, 2024)
The methodology for production of biologics is going through a paradigm shift from batch‐wise operation to continuous production. Lot of efforts are focused on integration, intensification, and continuous operation for decreased foot‐print, material, equipment, and increased productivity and product quality. These integrated continuous processes with on‐line analytics become complex processes, which requires automation, monitoring, and control of the operation, even unmanned or remote, which means bioprocesses with high level of automation or even autonomous capabilities. The development of these digital solutions becomes an important part of the process development and needs to be assessed early in the development chain. This work discusses a platform that allows fast development, advanced studies, and validation of digital solutions for integrated continuous downstream processes. It uses an open, flexible, and extendable real‐time supervisory controller, called Orbit, developed in Python. Orbit makes it possible to communicate with a set of different physical setups and on the same time perform real‐time execution. Integrated continuous processing often implies parallel operation of several setups and network of Orbit controllers makes it possible to synchronize complex process system. Data handling, storage, and analysis are important properties for handling heterogeneous and asynchronous data generated in complex downstream systems. Digital twin applications, such as advanced model‐based and plant‐wide monitoring and control, are exemplified using computational extensions in Orbit, exploiting data and models. Examples of novel digital solutions in integrated downstream processes are automatic operation parameter optimization, Kalman filter monitoring, and model‐based batch‐to‐batch control.